Change in Spatiotemporal Parameters During Running at Different Degrees of Inclination: Systematic Review - Patryk Marszałek; Krzysztof Przednowek; Cíntia França; Diogo V. Martinho; Adilson Marques; Gerson Ferrari; Wojciech Paśko; Élvio Rúbio Gouveia (Applied Sciences)
Background:Running is one of the simplest and most popular forms of exercise. Biomechanical evaluation of running is one of the elements of evaluating running technique and, consequently, improving sports performance. Running uphill and downhill is one of the components of daily running but also an element of training used by recreational runners. The aim of this study is to optimize running training and minimize the risk of injury by identifying changes in the spatiotemporal structure of running at different inclinations. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. The protocol has been registered on the international platform INPLASY under the number INPLASY202430094U2. The search was conducted up to 30 March 2024 using the Scopus, PubMed, and Web of Science databases. Results: Spatiotemporal parameters were most frequently analyzed at 2.8–3.35 m/s velocities and inclinations in the range of −11% to 11%. Decreases in stride length (SL) and flight time (FT), and increases in step frequency (SF) were the most frequently reported changes from all parameters analyzed as a function of inclination and velocity. Significant increases or decreases in individual parameters were more often observed for positive inclination values than negative ones. Conclusions: The heterogeneous results of the study limit the possibility of determining the changes that occur in the spatiotemporal structure of the run under the impact of different inclinations. The variation in the results for negative inclination values indicates the different characteristics of running uphill and downhill. However, for uphill running, SF, SL, and FT are closely related to the increase in inclination.